The Effect of H2S Pressure on the Formation of Multiple Corrosion Products on 316L Stainless Steel Surface - M. Shah; M. T. M. Ayob; R. Rosdan; N. Yaakob; Z. Embong; N. K. Othman (The Scientific World Journal)
H2S gas when exposed to metal can be responsible for both general and localized corrosion, which depend on several parameters such as H2S concentration and the corrosion product layer formed. Therefore, the formation of passive film on 316L steel when exposed to H2S environment was investigated using several analysis methods such as FESEM and STEM/EDS analyses, which identified a sulfur species underneath the porous structure of the passive film. X-ray photoelectron spectroscopy analysis demonstrated that the first layer of CrO3 and Cr2O3 was dissolved, accelerated by the presence of H2S-Cl-. An FeS2 layer was formed by incorporation of Fe and sulfide; then, passivation by Mo took place by forming a MoO2 layer. NiO, Ni(OH)2, and NiS barriers are formed as final protection for 316L steel. Therefore, Ni and Mo play an important role as a dual barrier to maintain the stability of 316L steel in high pH2S environments. For safety concern, this paper is aimed to point out a few challenges dealing with high partial pressure of H2S and limitation of 316L steel under highly sour condition for the oil and gas production system.